The Practices of Divorce by Petitions in Transmigration Area - Reftantia, Ghina; Sartika, Diana Dewi; Isyanawulan, Gita; Hapsari, Yuanita Dwi; Azzahri, Rizka; Yusda, Ihsanul Fuadi (Jurnal Sosiologi Andalas, 2025)
The divorce rate on Java Island tends to increase every year. These indicate a breakdown in marriages. But Javanese people do not only live in Java Island but are spread across many islands in Indonesia, primarily due to the transmigration program. Riau Province, situated on the island of Sumatra, is one of the areas designated for transmigration, resulting in a large number of Javanese people settling in these villages. It turns out that divorce cases are also common in these locations. Therefore, this study was conducted to examine the practice of divorce by petition among Javanese women in a transmigration village in Riau Province. The research approach employed in this study was qualitative, with an exploratory research style and a feminist methodology that prioritizes considering women's voices and experiences as worthy of being heard. The results of suggest that certain factors contribute to divorce, particularly in the context of marriage values within Javanese culture: legal system and women’s growing legal awareness, reinterpretations of Javanese familial and cultural values, economic independence and the gendered dimension of divorce, and the search for legal and social legitimacy. Even in transmigration areas far from Java Island, Javanese transmigrants and their descendants continue to uphold Javanese traditional values. These values persist and are internalized in their daily practices, including in the practice of divorce by petition in the transmigration area of Java.